Optimizing of partial porous structure for efficient heat transfer and thermal energy storage of phase change material in a rectangular cavity - Kiyak, Burak; Öztop, Hakan Fehmi (Springer, 2024)
This study investigates the effects of partial porous blocks integrated in a phase change material (PCM) in a rectangular cavity on the thermal performance of the system. Computational fluid dynamics simulations were used but validation was done by using experimental set-up and measurement of the results. Different thermal conditions of evolution effects of different configurations such as porous block orientation, number and porosity on the melting behaviour and energy storage capacity of PCM. For the base case, experimental and computational fluid dynamics results are well consistent. The analyses revealed that the horizontal placement of porous blocks significantly increases the melting rate and energy storage efficiency compared to the alone PCM. At Delta T = 15 degrees C, t = 160 min, the energy stored in the one-part horizontal porous block (1P-HPB) configuration is 11.17% higher than that in the alone PCM case.
Keywords: Porous material; Numerical analysis; PCM; Melting; Block; Experimental validation